Clinical experience of pelvic radiotherapy or chemoradiotherapy for postoperative uterine cervical cancer using intensity-modulated radiation therapy. (26th February 2020) - Yamamoto, Takaya; Umezawa, Rei; Tokunaga, Hideki; Kubozono, Masaki; Kozumi, Maiko; Takahashi, Noriyoshi; Matsushita, Haruo; Kadoya, Noriyuki; Ito, Kengo; Sato, Kiyokazu; Tsuji, Keita; Shimada, Muneaki; et al.
Abstract: The purpose of this study was to reveal treatment outcomes and toxicity after pelvic intensity-modulated radiotherapy (IMRT) for postoperative uterine cervical cancer of Japanese patients. Consecutive patients who were treated with pelvic IMRT for postoperative cervical cancer in our institute were retrospectively analyzed. Relapse-free survival (RFS) and overall survival (OS) were calculated using the Kaplan–Meier estimator, and log-rank tests were used to compare differences. From the database, 62 patients were identified. The pathology was squamous cell carcinoma in 44 patients and other pathology in 18 patients. Of the 62 patients, 35 had high-risk prognostic factors and 27 patients had intermediate-risk prognostic factors. The prescribed radiation doses were 50 Gy in 25 fractions for 58 patients and 50.4 Gy in 28 fractions for 4 patients. One patient received a vaginal cuff boost. Chemotherapy was administered in 36 patients. During the median follow-up period of 50.9 months, there was no locoregional failure. Six patients in the high-risk group relapsed, but none of the patients in the intermediate-risk group relapsed ( P = 0.02). The 3-year OS and RFS rates were 98.2% and 90.9%, respectively. Significant factors related to RFS were squamous cell carcinoma pathology ( P = 0.02), pathological T stage ( P = 0.04), surgical margin status ( P < 0.01) and multiple lymph nodes metastases ( P < 0.01). Grade 3 or more toxicity occurred in 6 patients. Four patients had obstruction of the intestine, and 2 patients had stenosis of the urinary tract. In clinical practice, the use of pelvic IMRT for postoperative cervical cancer of Japanese patients showed a low rate of toxicity without decreasing the efficacy.